2019
DOI: 10.7710/2162-3309.2250
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Journal Evaluation Tool to Evaluate the Credibility of Publication Venues

Abstract: INTRODUCTION A shared concern among librarians who work in an academic environment is finding effective mechanisms to help faculty identify suitable publication venues. Determining the suitability is now also complicated by the need to determine the credibility of the venue itself, to ensure that faculty select a venue that is held in esteem. DESCRIPTION OF PROJECT At Loyola Marymount University (LMU), a medium-sized, private institution in the United States, three librarians developed a tool to assist faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Check. Submit and a recently published checklist by Blas et al [27], would be beneficial for enhancing faculty skills in assessing journals [5].…”
Section: Discussionmentioning
confidence: 99%
“…Check. Submit and a recently published checklist by Blas et al [27], would be beneficial for enhancing faculty skills in assessing journals [5].…”
Section: Discussionmentioning
confidence: 99%
“…Many of those cater to specialized readerships. Although DOAJ attempts to list only valid OA journals, cautious authors can also apply the tools suggested by Blas, Rele, and Kennedy (2019) to check journals prior to publication. These examples illustrate free-to-read / free-to-publish OA funding approaches, which have persisted for many years.…”
Section: Plan S Problemsmentioning
confidence: 99%